Hound at the hospital - M. Baglio Ben 1960-; Ben M. Baglio (New York : Scholastic, 1998)
When Mandy and James observe SPCA inspector Danny Davies and his beagle, Sasha, on patrol, things taken an unexpected turn when Sasha is injured.
M
640